Dampak Usia Pemakaian PMS terhadap Kenaikan Suhu dan Kinerja Peralatan pada Gardu Induk - Aulidina Dwi Nur Andriyanti (Jurnal Mosfet, 2026)
Electric power generation is an important factor in an electrical system. The electrical energy that been generated, it would be distributed to consumers, both medium voltage and low voltage consumers. Before being distributed, the energy would be directed to substations to be managed and regulated by being increased, decreased, or divided. In substations, there were several protective devices that had function to protect equipment in the event of a disturbance, one of these devices is the PMS or disconnecting switch. This busbar disconnecting switch or PMS secured the system by separating the system from disturbances detection in the busbar. As the other electrical equipment, protective devices that have been used for a long time, it would lead to malfunction and decreasing of work. Therefore, this study focused on the condition of PMS that has been used for a long time, so this case could affect its temperature and performance. The researchers used a field study method for solving the problem. The result of this research showed that the long-term use of PMS could have an impact on decreasing performance and indicate the presence of hotspots and contact resistance exceeding the applicable standards.